Olfactory detection of methyl eugenol by male oriental fruit fly, Bactrocera dorsalis (Hendel) (Diptera: Tephritidae) - Chieng, Anna Chui-Ting (2019)
Oriental fruit fly, Bactrocera dorsalis (Hendel) is one of the world‟s most destructive pests of fruits and vegetables. Methyl eugenol (ME), a potent male attractant that is also found as a plant volatile compound, when mixed with insecticides is widely used to manage and control those pestiferous flies. Upon detection of ME, B. dorsalis male will respond rapidly by flying in zig-zag pattern to, landing and subsequent feeding on ME. Hitherto, with tremendous progress in molecular biology, there is now improved understanding in the molecular basis of insect detection of odourants such as ME by the antennae (ANT) of male B. dorsalis. However, little is known about the role of the maxillary palp (MP) in odourant detection. The general aim of this study was to evaluate the role of olfactory organs, ANT and MP in male B. dorsalis detection of ME. Therefore, the specific objectives of this study were to: 1) ascertain the function of MP in detection of ME by male B. dorsalis; 2) evaluate electrophoretic protein pattern in both MP and ANT, and following male attraction to ME, 3) evaluate associated proteome changes, 4) evaluate transcriptome changes followed by 5) an integrated proteo-transcriptome analysis. First, it has been demonstrated in those males from wind tunnel and cage behavioural assays that both olfactory organs were functionally complementary in detecting ME. The ANT was involved in long-range detection of ME while the MP at close range, manoeuvres the male towards the ME source for feeding. Second, exposure to ME appeared to have increased the protein concentration of both olfactory organs compared to those non-MEexposed. When protein profiles of the male olfactory organs were obtained using gradient PAGE, a number of proteins present were below 66 kDa. Similarly, SDS-PAGE analyses showed most protein bands were between 20- 100 kDa with 2 major bands below 20 kDa. No marked differences were seen in the protein patterns of both organs when compared between before, and after exposure to ME. Finally, a complementary approach using shotgun proteomics followed by transcriptomics (reference-based alignment) revealed the existence of 30 genes/ proteins having tissue specific expression with 7 being odourant binding proteins and 1 belonging to alcohol dehydrogenase. Six genes were significantly expressed in those organs with 5 up-regulated and 1 down-regulated. Of those 5 genes, BdorOBP69a was induced in both olfactory organs following the exposure to ME. Whilst BdorOBP69a was not detected in the proteome of both organs, another OBP BdorOBP84a-2 was significantly up-regulated in the MP only following exposure to ME. The presence of those different genes and proteins that were induced in different organs following exposure to ME suggests that the proteo-transcriptomic basis of gene-protein is an intricate pattern of operation. In genes that were involved in detoxification of xenobiotics including ME i.e., P450 members, two different types of those annotated genes were up-regulated at proteome level in both olfactory organs following exposure to ME. This suggests the role of MP in detecting and feeding on ME.